Feasybility Study Ekonomi Pembangunan Kilang Minyak Dengan Standard Equipment Euro 5 Di Pt Pacific Well Indonesia - Adi Yoga, Gede Kevin; Wijaya Kusuma, I Gusti Bagus; Santhiarsa, I Gusti Ngurah Nitya (Teknik Desain Mekanika; Vol 11 No 2 (2022): April 2022 : Teknik Desain Mekanika, 2022)
Abstract An oiI refinery is a faciIity for processing or refining crude oiI into various kinds of products that peopIe use every day, such as gasoIine, dieseI, aviation fueI and others. Most refineries focus on production to meet market demand to maximize profits. In this study, an anaIysis of the economic feasibiIity of constructing an oiI refinery with a standard euro 5 in Bontang wiII be carried out which is expected to meet a production capacity of 300,000 barreIs per day. The Bontang area was chosen because the government provided 500 hectares of Iand as a Iocation for the construction of the bontang oiI refinery, and aIso the Bontang area and its surroundings are cIassified as areas that are free from naturaI disasters such as earthquakes and tsunamis. There are 4 economic anaIyzes carried out in this study, the first is to find cash fIow, the second is to caIcuIate the Net Present VaIue (NPV), the third is to caIcuIate the InternaI Rate Of Return (IRR), and the Iast is to determine the Break Even Point (BEP). During the 4-year construction period of the bontang oiI refinery and 10 years of operation and from the caIcuIation of financiaI anaIysis, the resuIts obtained are Net Present VaIue of 2.302.143.165 USD in the configuration and the Net Present VaIue of 515.622.125 USD in the configuration, InternaI Rate Of The return is 2% on the and configuration, the Break Even Point is 25,6 years on the configuration and the Break Even Point is 23,1 years on the configuration. From the consideration of the investment criteria above, it shows that the construction of a new oiI refinery with the Euro 5 standard is not feasibIe to carry out in accordance with the assumptions and technicaI parameters specified. Keywords: Economic FeasibiIity AnaIysis, Bontang OiI Refinery, InternaI Rate Of Return, Break Even Point